Ritual innovation in the Hebrew Bible and early Judaism - MacDonald, Nathan (Beihefte zur Zeitschrift für die alttestamentliche Wissenschaft, 2016)
"What are rituals, if not ancient practices, unchanged throughout generations? Yet, if we compare the rituals described in late Second Temple texts to those in the Hebrew Bible it is apparent that rituals do change. Were such rituals practiced, or were they forms of textual imagination? How do rituals change and how are such changes authorized? Do textual innovation and ritual innovation relate?"--